GAMBARAN KARAKTERISTIK LUKA DAN PERAWATANNYA DI RUANGAN POLIKLINIK LUKA DI RS DR. WAHIDIN SUDIROHUSODO MAKASSAR - Huddu, Risma; Tahir, Takdir; Yusuf, Saldy (Jurnal Luka Indonesia, 2018)
Background: Injuries is something circumstances Where network continuity disconnected effect injury or surgery . The wound is divided to be two that is wound I and wound chronic . Every year number incident wound increasingly increased to become wrong one problem biggest if knowledge about care wound limited along with it care about wound . Introduction characteristics wound comprising of 13 BJWAT items and maintenance that is type dressinf and cleansing could help nurse for increase his knowledge related handling wound .Purpose: To knowing picture characteristics wound and maintenance in Room Dr. Wound Hospital Polyclinic Wahidin Sudirohusodo Makassar.Method: design research quantitative with design Cohort studies retrospect tif. The sampling technique used namely consecutive sampling with a total sample as many as 43 respondents . Data collection is done based on secondary data that is note record medical patient on visit first and last in Room Dr. Wound Hospital Polyclinic Wahidin Sudirohusodo Makassar.Result: From results research found that mostly patients who visit to clinic care wound is man as much as 72.09% (31 people), with type wound mostly is wound chronic . Results research on visit early with visit end no too significant changes that occur . Type dressings used mostly is Anti microbial as Primary dressing 37.2% (16 people ) , Natural fiber dressing as dressing secondary 81.4% (35 people ), and hypafix as dressing tert ier with amount 62.8 % ( 27 people ).Conclusions and Suggestions: characteristics wound very important for in value to get is known condition wound increasingly getting better or even increasingly worsening . By because that important for a nurse understand way rate characteristics wound and care wound .